صورة المرأة من خلال الإعلان: تسويق سافر لهيمنة الثقافة الذكورية - تنيو, فاطمة الزهراء (جامعة الوادي - University of Eloued, 2018)
الإعلانات التجارية هي وسيلة لتسويق المنتجات التجارية وتعتمد على الترغيب والإثارة. والملاحظ أن المرأة تشكل العنصر الأكثر إثارة في هذه الإعلانات من خلال التركيز على جسدها. حيث غالبا ما تعمد شركات الإعلان على إبراز هذا الجسد والإيحاءات الجنسية كوسيلة للترويج لمنتجاتها. فما هو حجم هذا الاستخدام لجسد المرأة؟ وما هي الصورة النمطية التي ترسخها هذه الإعلانات؟ وما مدى التوافق بين صورة المرأة المعروضة في الإعلانات مع صورتها في الذهنية المجتمعية؟ أين مسؤولية الإعلام الاجتماعية من هذا الاستخدام المبتذل لجسد المرأة؟ وكيف يمكن طرح صورة المرأة بشكل عصري وجميل بعيدا عن الابتذال؟ Commercial advertising is a means of marketing commercial products and is based on desir and excitement. It is obseved that women are the most important element in these advertisements by focusing on her body and sexual.... as a way to promote her products .What is the. of this use of women's bodies and what is the stereotype established by these ads? What is the compatibility between the image of women presented in advertisements and their image in the community mentality? Where is the social responsibility of media in this vulgar use of women's bodies? And how to put the image of women in a modern and beautiful away from the vulgarity.
The image of women in advertising :The obvious marketing of the male culture donination
مقال
Keywords: الصورة ، المرأة ، الإعلان ، التسويق ، الهيمنة; woman-image,advertising, merketing,domination